Výroba závěsu sedadla motocyklu - Hanych, Libor (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2016)
Práce předkládá návrh technologie výroby závěsu sloužícího k fixaci sedla motocyklu. Závěs je vyráběn z konstrukční oceli 1.0038 ve formě plechu tloušťky 1 mm ve výrobní sérii 50 000 ks/rok. Z jednotlivých variant výroby byla vybrána technologie stříhání a ohýbání ve sdruženém postupovém nástroji. Na základě literární studie technologie stříhání a ohýbání byl navržen optimální postup výroby závěsu. Po provedení technologických, konstrukčních a kontrolních výpočtů pro tyto technologie byl zkonstruován sdružený nástroj, pro který byla zpracována technická dokumentace. Pro výrobu byl zvolen výstředníkový lis LKDR 200 od firmy ŽĎAS. Tento lis vyhovuje z hlediska potřebné tvářecí síly i rozměrům nástroje. Ekonomickým zhodnocením byly stanoveny náklady na výrobu jednoho závěsu 18,5 Kč zahrnujících 35 % zisk podniku. Dle vypočteného bodu zvratu se výroba stává ziskovou po vyrobení 24 187 ks.

The project elaborates the design of technology production of the hinge used for fixing saddle motorcycle. The hinge is manufactured from 1 mm thick construction sheet steel 1.0038 in production run of 50 000 pcs/year. A technology of shearing and bending at progressive die tool was selected from various options as the most suitable technology of manufacturing. Based on the literature study of shearing and bending technology, an optimal production process of hinge was designed. After technological, structural and control calculations the tool was designed and the technical documentation was elaborated. The eccentric press LKDR 200 made by ŽĎAS company was selected for the production. This press complies in terms of required forming force and the dimensions of the tool. Using the economic evaluation, the production costs for one hinge were calculated in the amount of 18,5 CZK. 35% profit of the company is included in the price. According to the calculated turning point, the production becomes profitable after 24 187 piece being manufactured.
Production hinge saddle motorcycle
Keywords: Závěs; ocel 1.0038; stříhání; ohýbání; sdružený nástroj; Hinge; 1.0038 steel; shearing; bending; progressive die tool